Multicultural CSR Communication for Achieving a Sustainable Environment - Apriliani, Riski; Cassana, Rona Rizkhy Bunga; Ummah, Khanun Roisatul; Ramadhani, Dinda Safitri; Alhasanain, Nando (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2024)
Corporate Social Responsibility (CSR) plays a vital role in fostering an empowered and sustainable society, particularly concerning environmental conservation efforts. This study explores the implementation of CSR communication through a multicultural lens by PT Kilang Pertamina Internasional Refinery Unit II Sungai Pakning, focusing on its